GENERATION TRANSITION OF MEDICAL STUDENTS - Akbar, Resti; Adma, Azkira Zahara; Ortiz, Letizia Andrea; Anissa, Mutiara; Hariyani, Insil Pendri (Nusantara Hasana Journal, 2024)
Generations are groups of people who are born, grow, and maintain their lives over a certain period and are considered to have the same characteristics and points of view because they are influenced by events that occurred at that time. Generations themselves are classified based on year of birth. There are four generations are Baby Boomers, X Generation, Y Generation, and Z Generation. Each generation has different learning methods, styles, and attitudes. Medical educators have developed and implemented various teaching methods to develop students’ abilities more effectively and efficiently in future generations. However, there are barriers related to institutional resources, policies, and support that slow down the transition from traditional face-to-face classes to online classes. The transition itself began to be felt at the beginning of 2020, the Covid-19 pandemic caused very rapid changes, because it forced the implementation of fully online learning without face-to-face options. Students generally respond positively to the transition to online learning, but some students feel dissatisfied when learning online because they face stress and a huge workload. The end of the Covid-19 pandemic has resulted in digital transformation, such as hybrid learning and the medical learning process through mobile-based applications which makes it easier for students to learn from anywhere and at any time. It can be concluded that there are differences in learning methods, styles, and attitudes of medical students from generation to generation, this is due to the rapid development of technology and science, which makes the learning style of the current generation different from previous generations.